USING PROCESS WRITING APPROACH TO IMPROVE THE ABILITY OF MTS STUDENTS IN WRITING A RECOUNT TEXT - Amirudin Latif (Premise: Journal of English Education and Applied Linguistics, 2012)
This study was intended to improve the ability of the MTs Muhammadiyah 02 Pubian in writing a recount text by using process writing approach. They were guided to write recount texts through the five-step writing process namely prewriting, drafting, revising, editing, and publishing. The result showed that the students’ ability in writing recount texts was improved. In the end of Cycle 2, there were 22 out 30 students who obtained score > 60. Hence, the process writing approach is very effective to improve the students’ ability in writing recount texts.